PERHITUNGAN DANA PENSIUN DENGAN METODE PROJECTED UNIT CREDIT DAN INDIVIDUAL LEVEL PREMIUM - KUSUMA WARDHANI, I GUSTI AYU KOMANG; WIDANA, I NYOMAN; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika, 2014)
The company which provides the pension program needs the actuarial valuation to estimate the fund amount required by the company to pay for pension funding. Actuarial method that used in this research are projected unit credit and invidual level premium method. Through this research be obtained the result of valuation pension benefits with career average salary assumption is lower than the other salary assumptions. On the other hand, the result of normal cost final value valuation using individual level premium method is smaller than projected unit credit method that suits for the participants of the pension funding program.
Keywords: Pension Funding; Normal Cost; Projected Unit Credit; Individual Level Premium